2003
DOI: 10.1016/s0001-8791(02)00013-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and interest: Experimental studies of optimal incompetence

Abstract: How does self-efficacy affect interest? The interest-and-interests model assumes that factors that induce interest-novelty, complexity, conflict, and uncertainty-do so non-linearly. Self-efficacy should thus affect interest quadratically, because it reflects uncertainty about an activity's outcome. When self-efficacy is low, interest is low because the activity's outcome is certain. When self-efficacy is moderate, the person's success on the task seems likely, but not inevitable. But as self-efficacy becomes v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 33 publications
9
60
0
1
Order By: Relevance
“…Considering these explanations, we can say that the Turkish family structure and the collectivist culture are similar, based upon the perspective of the children and individuals' profile features. Thus, our finding is consistent, though it is surprising, and Carmichael, Callingham, Hay and Watson's (2010) study revealed that mathematics interest exhibits a quadratic connection with mathematical self-efficacy, in that those students who have high mathematical self-efficacy are aware that they can do mathematics tasks well, and in consequence will lose attention or interest (Silvia 2003), and many studies' finds (e.g. Pajares & Miller 1994;Güzel 2006) that recommended that students who have a high mathematical selfefficacy demonstrated higher mathematics performances than students who have a low mathematical self-efficacy and vice versa.…”
Section: Discussionsupporting
confidence: 80%
“…Considering these explanations, we can say that the Turkish family structure and the collectivist culture are similar, based upon the perspective of the children and individuals' profile features. Thus, our finding is consistent, though it is surprising, and Carmichael, Callingham, Hay and Watson's (2010) study revealed that mathematics interest exhibits a quadratic connection with mathematical self-efficacy, in that those students who have high mathematical self-efficacy are aware that they can do mathematics tasks well, and in consequence will lose attention or interest (Silvia 2003), and many studies' finds (e.g. Pajares & Miller 1994;Güzel 2006) that recommended that students who have a high mathematical selfefficacy demonstrated higher mathematics performances than students who have a low mathematical self-efficacy and vice versa.…”
Section: Discussionsupporting
confidence: 80%
“…However, concentration can be affected not only by interest but also by a variety of factors both inside and outside of learners, e.g., fatigue, stimulus strength, and time and place of learning. For difficulty and interest, Silvia [16] reported that both low and high in difficulty may cause low rating in interest, which implies that We take the same approach for the estimation of those three internal states. The ground truth values for all three internal states need to be gathered in terms of introspection, because the internal states cannot be physically measured by current technology in actual e-learning environments.…”
Section: Internal Statesmentioning
confidence: 99%
“…For instance, it has been found that interest in art is positively related to understanding the meaning of the artwork (e.g., provided via titles of abstract art or extra information about a poem; Millis, 2001;Silvia, 2005), given that people have sufficient time to process the meaning of the information (Leder, Carbon, & Ripsas, 2006). Also, research has shown that interest in an unclear task was highest when people experience moderate levels of selfefficacy, whereas low and high self-efficacy resulted in lower interest because the task was respectively too difficult or too easy (Silvia, 2003). In addition, in a theoretical analysis of technological change and product design, Rindova and Petkova (2007) argued that people might be better able to cope with novel technologies when they are presented in a familiar product design, because the familiarity makes it easier to comprehend.…”
Section: Complex Noveltymentioning
confidence: 99%